ANALYSING JOB DESIGN AND PERCEPTION TOWARDS GAMIFICATION APPROACH: CASE STUDY FOR AIESEC IN LILLE, FRANCE - Tirtoajie, Dimas Randy; Pangestu, Aria Bayu (Journal of Business and Management, 2021)
AIESEC Lille is a non-profit organization managed by Gen Z members to develop leadership skills to young people in Lille, France. Currently, the organization is experiencing issues regarding the members leaving and the overall activities being run in the organization. After conducting further assessments, it was found that AIESEC Lille had issues about the organization’s job design. The job design is one of the important aspects of the HR process, being the overall blueprint on how each task is given and completed. The job design can impact not just the organization’s well-being, but also the employees’ motivation, hence problems occur when employees are unmotivated in completing their work which can suspend the organization’s activities. The aim of this research is to analyze the current job design of AIESEC Lille and propose insights to help solve this problem, one of them by the approach of gamification. Throughout this study, an interview process was conducted followed by benchmarking to provide insights regarding the gamified job design. This research successfully pointed out the main problems within the job design, hence this research will provide further recommendations for the job design to be created in AIESEC Lille.Keywords: Job design, Gamification Approach, Gen Z